Shaping of the axiological status of Tomos in Ukrainian religious media discourse in the light of cognitive linguistics and rhetoric - Levko, Oleksandr (Current issues of Ukrainian linguistics: theory and practice, 2019)
The paper is focused on the cognitive mechanisms underlying the construction of axiological status of Tomos and autocephaly of the Ukrainian Orthodox Church in Ukrainian religious media discourse of the last few months from the standpoint of cognitive linguistics and rhetoric. The data used for the study are interviews, announcements and other media texts of the UOC (MP) and UOC (KP) leaders and spokesmen, published on respective official websites of each jurisdiction in 2018. As a result of our study, it was found out that discussions around Tomos and autocephaly gave birth to new allusion-based phraseological units in Ukrainian media space, while also actualizing the use of religious terms which had been previously unknown to average citizens, such as "Tomos", "autocephaly", "canonicity", "Eucharistic communication", "Ecumenical Patriarch" etc. In the media context, these specific terms of the Church law have acquired axiological connotations, turning into axiologems and anti-axiologems. It was also revealed that the argumentation of the positive / negative axiological status of Tomos and autocephaly in Ukrainian religious mass media largely relies on cognitive metaphors and metonymies. In the media context, these cognitive mechanisms of knowledge categorization are of great importance in swaying the public opinion and affecting the value system of the audience. In the texts under study, the most common cognitive metaphors are "Church is body", "Church leaders are doctors", "Intra-Orthodox relations are war", "Intra-Orthodox relations are play", while the most prominent cognitive metonymy is geographical metonymy, whereby the agency is transferred to location. The most productive source domains for the metaphors, which serve to express the evaluation of current processes in the Church, turn out to be human body, medicine, war, play and crime. Decisions of Church leaders regarding Tomos are conceptualized as right or wrong diagnosis and treatment for an illness, expansionist policies or war for peace, raider attack or fair / unfair play. In the media texts produced by both sides, negative connotations are also conveyed via geographical metonymy, when the Constantinople Patriarchate is substituted for by Fanar or Istanbul, whereas the Moscow Patriarchate is referred to as Moscow or Kremlin. We have come to the conclusion that cognitive metaphors and metonymies in Ukrainian religious media discourse are used with the purpose of increasing the persuasive effect of the text and swaying the audience towards adopting the viewpoint of the addresser.
Keywords: cognitive metaphor, cognitive metonymy, religious media discourse, axiologeme, values, Tomos, autocephaly.